Would You Impugn My Justice? A Nuanced Approach to the Hebrew Bible's Theology of Divine Recompense. (July 2015) - Kaminsky, Joel S.
Recent scholarship has tended to see the book of Job as sweeping away an earlier, mechanistic theology of divine recompense. This essay argues that the widespread biblical notion that God rewards the righteous and punishes the wicked is more complex than generally recognized and that recovering its nuances not only helps one better understand the theological outlook of books like Deuteronomy, Proverbs, and Psalms, but also helps one better grasp the debates within Job. The essay is framed by some reflections on why our contemporary culture regularly misreads the Bible's language of divine retribution in spite of the fact that many contemporary readers affirm analogous ideas of reward and punishment.